ADAPTIVE CHANGES IN THE DURATION OF CYCLIC PREFIX OFDM SYMBOLS WITH MULTIPATH PROPAGATION OF RADIO SIGNALS. - Конахович, Г.; Марченко, О.; Орадченко, Р. (Science-based technologies, 2012)
Methods to combat intersymbol interference in channels with multipath propagation of radio signals. An algorithm of adaptive changes in the duration of cyclic prefix OFDM symbols, allowing to choose the shortest prefix to ensure maximum permissible effective data rates for a given quality customer service.